The 3D genome landscape: Diverse chromosomal interactions and their functional implications - Fleck, Katherine; Raj, Romir; Erceg, Jelena (Frontiers in Cell and Developmental Biology, 2022)
Genome organization includes contacts both within a single chromosome and between distinct chromosomes. Thus, regulatory organization in the nucleus may include interplay of these two types of chromosomal interactions with genome activity. Emerging advances in omics and single-cell imaging technologies have allowed new insights into chromosomal contacts, including those of homologs and sister chromatids, and their significance to genome function. In this review, we highlight recent studies in this field and discuss their impact on understanding the principles of chromosome organization and associated functional implications in diverse cellular processes. Specifically, we describe the contributions of intra-chromosomal, inter-homolog, and inter-sister chromatid contacts to genome organization and gene expression.